Waste to Product : Bisolum-Bricks, Incorporating of WWTP Sludge of Textile Industry into Bricks for Wall Pairs - Armas Arifin Arbunowo; Purwanto Purwanto; M. Arief Budihardjo (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2019)
The disposal of WWTP sludge is one of problems in textiles industry, which requires serious attention to find a way out. Utilization of sludge from the textile industry wastewater treatment, according to the Republic of Indonesia Goverment Regulation No.110 year 2014, can be used as a mixture of brick raw materials, must consider the availability of technology, meet environmental quality standards and meet technical requirements for use. Environmental feasibility refers to Goverment Regulation No.110 year 2014, carried out with TCLP toxicity tests on raw materials for soil, WWTP sludge and brick products. Acute toxicity test LD 50, carried out on brick products in which using a mixture of WWTP Sludge. Technical feasibility is carried out by testing the quality of brick products in accordance with solid brick Nasional Indonesian Standard (SNI) for wall pairs. Research results prove the toxicity test on raw materials and brick products with a mixture of up to 60% of waste, still meets the requirements of TCLP and LD.50 according to GR No.110 year 2014. Test the quality of bricks at the use of 40% and 60% mixture of sludge still meet Nasional Indonesian Standard (SNI 15-2094-2000) solid red brick for wall pairs.